2015
DOI: 10.1287/opre.2015.1416
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Sparse Designs for Process Flexibility via Probabilistic Expanders

Abstract: We study the problem of how to design a sparse flexible process structure in a balanced and symmetrical production system to match supply with random demand more effectively. Our goal is to provide a sparsest design to achieve (1 − ϵ)-optimality relative to the fully flexible system. In a balanced system with n plants and n products, Chou et al. (2011) proved that there exists a graph expander with O(n/ϵ) arcs to achieve (1 − ϵ)-optimality for every demand realization. Wang and Zhang (2015) showed that the sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…to a few generalized expansion properties of graphs constructed using the TPC (see Section 4.1). These generalized expansion properties extend the notion of "probabilistic expanders" in Chen et al (2015). In fact, they can be viewed as a continuous generalization of the probabilistic expansion property, which is based on the cardinality of a set of nodes.…”
Section: Main Results -Optimal Construction and Technical Contributionsmentioning
confidence: 96%
See 2 more Smart Citations
“…to a few generalized expansion properties of graphs constructed using the TPC (see Section 4.1). These generalized expansion properties extend the notion of "probabilistic expanders" in Chen et al (2015). In fact, they can be viewed as a continuous generalization of the probabilistic expansion property, which is based on the cardinality of a set of nodes.…”
Section: Main Results -Optimal Construction and Technical Contributionsmentioning
confidence: 96%
“…By choosing the linkage probability so that each node has an average degree of O(ln(1/ )), Chen et al (2015) showed that the uniform probabilistic construction achieves (1 − )optimality w.h.p. Moreover, such a construction is asymptotically optimal, which means it has the fewest possible edges for achieving (1 − )-optimality w.h.p.…”
Section: Main Results -Optimal Construction and Technical Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expansion property has been used as a surrogate metric for structure connectivity, and has been proved to be effective in balanced flexibility design problems (Chen et al 2015, Chou et al 2011. In this section, we show that the expansion property, with a proper extension, is also critical to reliable flexibility design problems.…”
Section: Sufficient Conditions For Achieving the Performance Criterionmentioning
confidence: 93%
“…They prove by a randomized algorithm that there exist graph expanders with O(n/) edges that achieve (1 À )-optimality in the worst case in balanced and symmetric systems with bounded demands. Chen et al (2015) develop a new variant of the graph expandersprobabilistic expanders, and show that the probabilistic expanders are sparser than the graph expanders, with only O(n ln (1/)) edges necessary, to achieve (1 À )-optimality with high probability, which is a stronger concept of optimality relative to the (1 À )-optimality in expectation.…”
Section: Literature Reviewmentioning
confidence: 99%